Cavalrymen and their Horses during the American Indian Wars - Lee Farren (Symphony in the Flint Hills, 2013)
Excerpt from "Cavalrymen and their Horses during the American Indian Wars." From 1866 to 1891, ten US Cavalry regiments fought a dozen major campaigns against the American Indians of the western United States.
Keywords: cavalry; war; Indians; Native American; army; military; cavalrymen; horses; skirmish; Civil War; troops; American Indian War; riding; gear; company; Calico Troop; Brindles; fight; saddle; officer